Оксинитридные тонкие пленки, осажденные реактивным магнетронным распылением и их применение в биомедицине; Взаимодействие ионов с поверхностью (ВИП-2023); Т. 2 - Карелин С. Ю. Станислав Юрьевич; Юдинцев П. В. Петр Владимирович; Филимонова В. С. Валерия Сергеевна; Краснобаева Л. А. Лариса Александровна; Гусакова С. В. Светлана Валерьевна; Лисичко Е. В. Елена Владимировна; Никитенков Н. Н. Николай Николаевич; Сыпченко В. С. Владимир Сергеевич (Ионно-индуцированные процессы в тонких пленках и наноструктурах, 2023)
In the paper, we investigate the structure, elemental and phase composition Ti-O-N coatings that were deposited by reactive magnetron sputtering on a stainless steel surface. The film consists of two phases: a nanocrystalline and amorphous structure, the strength of the interfaces increases the resistance to deformation of the coating, and the absence of dislocations inside the crystallites increases their elasticity. At saturation in the plasma on the surface of the films formed oxy-hydrides.